Spatial light modulator technology materials, devices, and applications - Efron, Uzi (Optical engineering (Marcel Dekker, Inc.), 1995)
This work offers comprehensive coverage of all aspects of spatial light modulators, from the various optical materials used for modulation, through the availability and characteristics of specific devices, to the main applications of SLMs and related systems. The gamut of SLMs is surveyed, including multiple-quantum-well, acousto-optical, magneto-optical, deformable-membrane, ferroelectric-liquid-crystal and smart-pixel modulators.